Relationship between management factors with days open in crossbred cattle and constraints faced by dairy farmers of Karnataka - Chandrashekhar, GK; Satyanarayan, K; Jagadeeswary, V; Shilpashree, J (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present study on relationship between management factors in crossbred cattle and days openas well as the constraints faced by dairy farmers was purposively conducted in Bengaluru rural district of Karnataka.The data were collected using a structured pretested interview schedule from 120 respondents selected randomly from four taluks viz; Devanahalli, Doddaballapur, Hoskote and Nelamangala. The study revealed that number of artificial insemination (AI) in relation to conception and voluntary waiting period had a positive significant correlation to days open in dairy cattle. Lack of awareness on deworming of cattle was the major constraint among the respondents. Hence, the authors conclude that extension activities like meetings, discussions, mass media, etc. are to be planned and conducted by extension agencies to increase knowledge and thereby adoption of recommended practices leading to increase production and income generation.
Keywords: Crossbred Cattle; Management; Days Open; Constraints